Antimicrobial drug susceptibility testing for the management of Helicobacter pylori infection in personalized eradication therapy - Gou, Lingzhu; Ma, Zenghui; Han, Mengyu; Tian, Wenji; Chen, Xinglan; Kang, Xiaojuan; Zhang, Dekui (Frontiers in Microbiology, 2025)
Helicobacter pylori is a gram-negative bacterium that associated with diseases such as gastritis, peptic ulcer and gastric cancer. In recent years, various treatment options have been evaluated, such as bismuth-containing quadruple therapy, high-dose dual therapy, and the use of acid-suppressing drugs such as Vonoprazan, however, the effectiveness of H. pylori eradication treatment is still dramatically decreasing due to the rising antibiotic resistance rate, and successful eradication of H. pylori has become a major public health problem. Therefore a promising strategy against drug-resistant H. pylori is to individualize treatment based on the outcome of antibiotic resistance. This article reviews the antibiotic resistance situation in recent years in various regions. The advantages and disadvantages of novel antibiotic resistance detection methods are examined, and the therapeutic efficacy of individualized therapy under different detection methods is evaluated. Molecular methods have developed rapidly in recent years, and non-invasive methods can quickly and accurately determine the presence of drug resistance. Clinical application of antibiotic resistance test results to guide medication use needs to be used as early as possible. Customized therapies based on antibiotic drug sensitivity testing and individualized therapies guided by personal medication history can contribute to future therapeutic strategies.